POLITENESS STRATEGIES IN SUNDANESE CONTEXT - Ayang Winda Sri Widianingsih (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
This research aims on the refusal and acceptance strategies, as well as their politeness, in the context of a sundanese community in Kuningan. The study was formulated to answer research questions (1) what are the types of refusal and accepance strategies used in Sundanese context?. (2) how is the politeness strategies happen in sundanese context?. This study employed the qualitative method as research design. A Discourse Completion Task (DCT) is employed to collect data from 20 respondents. Because the respondents are Sundanese, the questionnaire is written in Bahasa Sunda, making it easier to evaluate. The results show that there are 240 utterances, 150 of which are refusing and 90 of which are accepting. The refusal strategies are made up of 12 techniques, whereas the acceptance strategies are made up of 6 techniques. Most Sundanese respondents are courteous, as seen by their responses when requesting to follow their professor or when refusing to speak to a person of great power. So they know where they should be courteous and who they should talk to.